2022
DOI: 10.3390/jcm11144004
|View full text |Cite
|
Sign up to set email alerts
|

Using Minimum Redundancy Maximum Relevance Algorithm to Select Minimal Sets of Heart Rate Variability Parameters for Atrial Fibrillation Detection

Abstract: Heart rate is quite regular during sinus (normal) rhythm (SR) originating from the sinus node. In contrast, heart rate is usually irregular during atrial fibrillation (AF). Complete atrioventricular block with an escape rhythm, ventricular pacing, or ventricular tachycardia are the most common exceptions when heart rate may be regular in AF. Heart rate variability (HRV) is the variation in the duration of consecutive cardiac cycles (RR intervals). We investigated the utility of HRV parameters for automated det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…We have previously used the same data, consisting of RR intervals from over 60,000 1-min ECG segments with either AF or SR, in our studies [ 2 , 3 ]. In [ 2 ], we selected various HRV indices for the machine learning algorithms, whereas in [ 3 ], we determined the optimal x for pRRx. Although using the same database for different studies has some limitations, it also has practical benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously used the same data, consisting of RR intervals from over 60,000 1-min ECG segments with either AF or SR, in our studies [ 2 , 3 ]. In [ 2 ], we selected various HRV indices for the machine learning algorithms, whereas in [ 3 ], we determined the optimal x for pRRx. Although using the same database for different studies has some limitations, it also has practical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Many various heart rate variability (HRV) parameters are used alone or in combinations to distinguish atrial fibrillation (AF) from sinus rhythm (SR) [ 1 , 2 , 3 ]. We and some other authors have shown that the percentage of successive RR interval differences equal to or greater than 50 ms (pRR50) outperforms other HRV parameters for this purpose [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the enormous dimensionality of the dataset utilized in the proposed system, we implemented feature selection using the feature ranking technique in GNU Octave. The maximum relevance minimum redundancy method (mRMR) [ 33 ] is a feature extraction and selection method and helps to reduce computing complexity and create models with the best generalization, and it tends to improve the classifier’s learning efficiency [ 34 ]. In binary classification using τ-tests for independent precedents, feature selection plays a vital role between the classes.…”
Section: Methodsmentioning
confidence: 99%
“…Due to different distributions of HRV-derived parameters in AF and SR [ 8 ], HRV has gained new interest in AF detection in ECG [ 9 , 10 , 11 ], as well as from wearable devices [ 12 , 13 ]. Several authors used feature selection methods to find the most relevant HRV parameters for AF detection [ 14 , 15 ]. Others incorporated HRV to predict future occurrence of AF [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%